Traditional Farming Lifestyle in Old Older Mennonites Modulates Human Milk Composition - Seppo, Antti E.; Choudhury, Rakin; Pizzarello, Catherine; Palli, Rohith; Fridy, Sade; Rajani, Puja Sood; Stern, Jessica; Martina, Camille; Yonemitsu, Chloe; Bode, Lars; Bu, Kevin; Tamburini, Sabrina; et al. (Frontiers in Immunology, 2021)
Background: In addition to farming exposures in childhood, maternal farming exposures provide strong protection against allergic disease in their children; however, the effect of farming lifestyle on human milk (HM) composition is unknown. Objective: To characterize the maternal immune effects of Old Order Mennonite (OOM) traditional farming lifestyle when compared to Rochester (ROC) families at higher risk for asthma and allergic diseases using HM as a proxy. Methods: HM samples collected at median 2 months of lactation from 52 OOM and 29 ROC mothers were assayed for IgA1 and IgA2 antibodies, cytokines, endotoxin, HM oligosaccharides (HMOs), and targeted fatty acid (FA) metabolites. Development of early childhood atopic diseases in children by 3 years of age was assessed. In addition to group comparisons, systems level network analysis was performed to identify communities of multiple HM factors in ROC and OOM lifestyle. Results: HM contains IgA1 and IgA2 antibodies broadly recognizing food, inhalant and bacterial antigens. OOM HM has significantly higher levels of IgA to peanut, ovalbumin, dust mites, and Streptococcus equii as well TGF-β2, and IFNλ3. Path-based analysis of HMOs shows lower activity in the path involving lactoneohexaose LNH in the OOM as well as higher levels of lacto-N-neotetraose (LNnT), and two long-chain FAs C-18OH (stearic acid), and C-23OH (tricosanoic acid) compared to Rochester HM. OOM and Rochester milk formed five different clusters, e.g. butyrate production was associated with Prevotellaceae, Veillonellaceae and Micrococcaceae cluster. Development of atopic disease in early childhood was more common in Rochester and associated with lower levels of total IgA, IgA2 to dust mite as well as of TSLP. Conclusion: Traditional, agrarian lifestyle and antibiotic use are strong regulators of maternally derived immune and metabolic factors, which may have downstream implications for postnatal developmental programming of infant’s gut microbiome and immune system.